P-BN57 The impact of COVID-19 pandemic on management of patients with acute uncomplicated gallstone pancreatitis. (16th December 2021) - Staniszewska, Aleksandra; McCready, Rebekah; Grocock, Christopher; Gunasekera, Rohan; Hartley, Mark; Howes, Nathan; Stephens, Nathan; Rao, Rohith
Abstract: Background: Current British Society of Gastroenterology guidelines suggest that patients presenting with acute uncomplicated gallstone pancreatitis should ideally undergo laparoscopic cholecystectomy during the index admission or within two weeks of discharge from hospital. COVID-19 pandemic had a significant impact on the delivery of elective and semi-elective surgical services in the National Health Service (NHS) due to limited availability of theatre resources. The aim of this study was to evaluate compliance with the BSG guidelines during the COVID-19 pandemic and the impact of the newly introduced `Hot' lists at our centre. Methods: Patients admitted with first presentation of acute uncomplicated gallstone pancreatitis between 01/03/19 and 25/02/21 were identified from electronic records. Pregnancy and lack of fitness for surgery were the exclusion criteria. Patients admitted between 01/03/19 and 31/12/19 were defined as the pre-COVID cohort. Those admitted between 23/03/20 and 25/02/21 formed the COVID cohort and had access to urgent gallbladder lists. Baseline characteristics, choice of imaging and timing of laparoscopic cholecystectomy were compared between the two cohorts using STATA software. Continuous variables were compared with Mann Whitney test and categorical variables were compared with Pearson's Chi-Squared test. Results: 53 patients were identified in the total cohort with 27 being hospitalised prior to COVID-19 outbreak and 26 presenting after the national lockdown. Baseline characteristics did not differ significantly between the two groups.  Biliary imaging pathway was similar between the two cohorts and importantly there appeared to be no delays in radiological tests during the lockdown. The overall proportion of patients undergoing cholecystectomies remained similar between the two groups and percentage of patients having it during the index admission did not differ. However, patients undergoing cholecystectomy post discharge had a significantly shorter waiting time during the lockdown (p = 0.021) as they were prioritised on the 'Hot lists' created to meet the demands of reduced planned theatre service. Conclusions: During the 2020 COVID pandemic our service for patients with uncomplicated gallstone pancreatitis continued to be delivered. Despite clinical pressures, there were no notable delays in biliary imaging. The introduction of the urgent operating lists has significantly reduced the time to laparoscopic cholecystectomy following admission for patients with acute uncomplicated gallstone pancreatitis during this period.